2018
DOI: 10.5045/br.2018.53.3.198
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of lymphocyte subsets in newly diagnosed acute myeloid leukemia

Abstract: BackgroundTumor-infiltrating lymphocytes, which form a part of the host immune system, affect the development and progression of cancer. This study investigated whether subsets of lymphocytes reflecting host-tumor immunologic interactions are related to the prognosis of patients with acute myeloid leukemia (AML).MethodsLymphocyte subsets in the peripheral blood of 88 patients who were newly diagnosed with AML were analyzed by quantitative flow cytometry. The relationships of lymphocyte subsets with AML subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The immune system plays an important role in eliminating malignant cells through immune surveillance (46). Several studies have reported abnormal changes in the relative frequency and function of lymphocytes, especially T cells, in AML (47,48). CAR-T cells can specifically kill tumor cells without the limitations of major histocompatibility complex.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system plays an important role in eliminating malignant cells through immune surveillance (46). Several studies have reported abnormal changes in the relative frequency and function of lymphocytes, especially T cells, in AML (47,48). CAR-T cells can specifically kill tumor cells without the limitations of major histocompatibility complex.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CD8 + T cells could effectively restore T cell function and improve their antitumor activity by inhibiting ferroptosis (Ma et al, 2021). Moreover, there is emerging evidence that a high proportion of natural killer (NK) cells is associated with death before remission (Park et al, 2018). However, the degree to which ferroptosis influences survival and treatment strategy of AML remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…High white blood cell (WBC) index is a prognostic factor for AML [9]. High percentages of CD19+ B cells in newly diagnosed AML patients were reported to be unrelated to DFS and OS [10]. However, it has been reported that the transitional B cell frequency of patients with AML was higher than that of healthy controls, and patients sampled further from the end of chemotherapy had lower transitional B cell frequency [11].…”
Section: Introductionmentioning
confidence: 99%